Asas Kepastian Hukum Pelaksanaan Hukuman Mati di Indonesia - Agatha Jumiati; Ellectrananda Anugerah Ash-shidiqqi (Prodi Ilmu Hukum, Universitas Teuku Umar, 2022)
This article aims to examine aspects of legal certainty and justice in the application of the death penalty in Indonesia, as well as the concept of legal and fair deadlines for executions. Using normative judicial methods, this article shows that current law does not reliably and fairly determine when the death penalty should be executed. Due to time constraints, the legal certainty and justice of those sentenced to death are not guaranteed. Therefore, it is necessary to revise the laws and regulations for execution in the basic criminal law, public criminal law, and statutory law.